Identification and characterization of fungal species causing sheath blight diseases on paddy ( Oryza sativa L. ) - Mahusin, Mawardi (2016)
Sheath blight disease is one of the major problem faced by paddy growers particularly in the tropics. The sheath blight disease became a major problem when the high-yielding rice cultivars were introduced in tropical Asia. Also, the pathogen causing this disease is favors warm temperature and high humidity conditions. This pathogen infects the leaf sheaths at the lower leaves near the water line. Later, these lesions expand, appear water-soaked lesions, and eventually the lesions turn brown-to-tan and dry out of sheaths. This study were focusing on isolation of fungal pure culture, then identify fungal pathogens to species level based on morphological characteristics and polymerase chain reaction (PCR) protocol using ITS4 and ITS5 primers and also to construct internal transcribed spacer (ITS) phylogeny of the isolated fungal species. To accomplish these objectives, infected paddy plants were collected and isolated on potato dextrose agar (PDA) and observing in vitro morphological and physiological characteristics. The morphological observation resulting in the detection of Rhizoctonia solani characteristics. To ensure the morphological result and determine the pathogen to species level, molecular observation were done by extracting the DNA genomic from fresh fungal mycelium using the CTAB protocol. The internal transcribed spacer (ITS) region of the ribosomal DNA was amplified using primers ITS4/ITS5. The PCR products of the ITS were sequenced and analyzed using BLAST nucleotide query in GenBank. The result obtained from molecular observation approving the fungal species claimed from morphological observation that causing sheath blight diseases on paddy is Rhizoctonia solani. This study is a significant step forward toward management recommendations in controlling sheath blight disease in rice-growing regions in Malaysia and adds information on the genetic diversity of this pathogenic fungi causing sheath blight disease.